Social Justice Advocacy and Ethical Sensitivity of Nursing Students: A Descriptive Research. - Kocakurt, Feyza; Akın, Belgin (Lokman Hekim Health Sciences, 2023)
Introduction: In a holistic social defense theory, nurses should defend not only patients in hospitals but also society. The aim of the study was to determine the social justice advocacy (SJA) levels of nursing students in their first, second, third, and fourth years in a private university and to analyze the relationship of SJA with sociodemographic and academic characteristics and ethical sensibility (ES). Methods: This study was descriptive and was conducted in Ankara in Lokman Hekim University, Faculty of Health Sciences, Nursing Department, during the academic year 2021-2022. It comprised students (n=167) who studied in the classroom. The data of this study were collected by the Survey Form, the Scale of Social Justice Defense, and the Ethical Sensitivity Survey. Results: When the SJA scores of the participants according to the class they studied were examined, a significant difference was found between the SJA scores of the fourth graders and the first and second grades (p=0.019). When the scores of the participants from the Moral Sensitivity Questionnaire were compared with the scores they obtained from the SJA Scale subscales, a very weak (r=-0.238) and statistically significant negative correlation was found between the scores they obtained from the Moral Sensitivity Questionnaire and the scores they received from the Applicant's Empowerment subscale. Discussion and Conclusion: There are very little scientific data about SJA and the relationship of nurses in our country with ES, and it is recommended to do more work to study the knowledge and skills of nursing students on SJA.